2012
DOI: 10.1590/s1984-82502012000100004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of LDL-oxidation and antioxidant properties related to polyphenol content of hydrophilic fractions from seaweed Halimeda Incrassata (Ellis) Lamouroux

Abstract: LDL oxidation and oxidative stress are closely related to atherosclerosis. Therefore, natural antioxidants have been studied as promising candidates. In the present study, the LDL oxidation inhibition activity of bioactive compounds from Halimeda incrassata seaweed. associated to antioxidant capacity, was evaluated in vitro. Experimental work was conducted with lyophilized aqueous extract and phenolic-rich fractions of the seaweed and their effect on LDL oxidation was evaluated using heparin-precipitated LDL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Yeh and Yen (2006) suggested that these three phenolic acids, including ferulic acid, modulate the phase II antioxidant enzymes and the phase II sulphate conjugative enzymes; and they seem to selectively induce hepatic mRNA transcripts for CAT, probably through the up-regulation of gene transcription, as well as the Nrf2 transcription factor. In previous results from our group, Mancini-Filho et al (2009) reported an over-expression of CAT genes by treatment with FPA from Halimeda monile; while de Oliveira e Silva et al (2012) showed that by using (RT/PCR) analysis increased the catalase (CAT) gene expression in the group treated with free phenolic acid (FPA) fractions from Halimeda opuntia, suggesting inducing effects on the enzyme.…”
Section: Expression Of Cat Hepatic Enzymes By Pcr-rtmentioning
confidence: 86%
See 1 more Smart Citation
“…Yeh and Yen (2006) suggested that these three phenolic acids, including ferulic acid, modulate the phase II antioxidant enzymes and the phase II sulphate conjugative enzymes; and they seem to selectively induce hepatic mRNA transcripts for CAT, probably through the up-regulation of gene transcription, as well as the Nrf2 transcription factor. In previous results from our group, Mancini-Filho et al (2009) reported an over-expression of CAT genes by treatment with FPA from Halimeda monile; while de Oliveira e Silva et al (2012) showed that by using (RT/PCR) analysis increased the catalase (CAT) gene expression in the group treated with free phenolic acid (FPA) fractions from Halimeda opuntia, suggesting inducing effects on the enzyme.…”
Section: Expression Of Cat Hepatic Enzymes By Pcr-rtmentioning
confidence: 86%
“…Several lines of results have documented the ability of a hydrophilic extract from this seaweed to target free-radical mediated processes in vitro cell culture and in vivo experimental models (Rivero et al, 2003;Fallarero et al, 2003;Linares et al, 2004;Mancini-Filho et al, 2009;de Oliveira e Silva et al, 2012). In previous studies, in vitro Halimeda spp seaweeds have been described as having a relationship between antioxidant activity and antiatherogenic properties (Costa-Mugica et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The functional groups of flavonoids attached to the three ring system of flavonoids has been reported to trigger a positive impact against LDL oxidation [21]. In a study by Naderi et al Costa-Mugica et al [71] reported that lyophilized aqueous extracts and phenolic-rich fractions of seaweed (H. Incrassata) significantly inhibited LDL oxidation when evaluated by using heparinprecipitated LDL exposed to Cu2+ ions with AAPH as the free radical generator. The authors claimed that the observed effect could be related to the antioxidant potential of the polar phenolic fractions.…”
Section: Effect Of Flavonoids Phenolic Acids and Antioxidant Mixturesmentioning
confidence: 99%
“…The aqueous extracts from Halimeda incrassata and Bryothamnion triquetrum seaweeds have been reported as antiatherogenic [7] and antinociceptive and anti-inflammatory [8,9], respectively. Additionally, both extracts contain neuroprotective and antioxidant capacities [10][11][12] and some experimental works have been carried out in order to evaluate their toxic properties, by means of in vitro assays [13][14][15]. The present study was designed to test the genotoxic potential of these aqueous extracts in the primary structure of DNA molecule.…”
Section: Introductionmentioning
confidence: 99%